Epidemiological Characterization of the 2017 Dengue Outbreak in Zhejiang, China and Molecular Characterization of the Viruses - Yan, Hao; Ding, Zheyuan; Yan, Juying; Yao, Wenwu; Pan, Junhang; Yang, Zhangnv; Lou, Xiuyu; Mao, Haiyan; Lin, Junfen; Sun, Jimin; Hou, Juan; Wu, Haocheng; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Dengue, a mosquito-borne disease caused by the dengue virus (DV), has been recognized as a global public health threat. In 2017, an unexpected dengue outbreak occurred in Zhejiang, China. To clarify and characterize the causative agent of this outbreak, data on dengue fever cases were collected from the China Information System for Disease Control and Prevention in Zhejiang province for subsequent epidemiological analysis. A total of 1,229 cases were reported, including 1,149 indigenous and 80 imported cases. Most indigenous cases (1,128 cases) were in Hangzhou. The epidemic peak occurred in late August and early September, and the incidence rate of elderly people (4.34 per 100,000) was relatively high. Imported cases were reported all year round, and most were from South-East Asia and Western Pacific regions. Young people and men accounted for a large fraction of the cases. Acute phase serums of patients were collected for virus isolation. And 35 isolates (including 25 DV-2, 8 DV-1, 1 DV-3, and 1 DV-4) were obtained after inoculation and culture in mosquito C6/36 cells. The E genes of the 35 new DV isolates and the complete genome of a DV-2 isolate (Zhejiang/HZ33/2017), and the E gene of a DV-2 isolate from Ae. albopictus (Zhejiang/Aedes-1/2017) were determined. Phylogenetic analyses were performed using the neighbor-joining method with the Tajima-Nei model. Phylogenetically, DVs of all four serotypes with multiple genotypes (mainly including 21 Cosmopolitan genotype DV-2, 4 Asian I genotype DV-2, 6 genotype I DV-1, and 2 genotype V DV-1) were present in the indigenous and imported cases in Zhejiang during the same period. Most of the isolates probably originated from South-East Asia and Western Pacific countries. The imported cases, high density of mosquito vector, and missed diagnosis might contribute to the 2017 outbreak in Zhejiang.